(untitled) (Journal of Plant Disease Sciences, 2019)
Cotton leaf curl virus disease (CLCuD) is the disease of major importance in cotton leads to the yield loss in the South Western Region of Punjab. All the Bt cotton hybrids are more or less susceptible to the Cotton leaf curl virus disease but their severity varied. The studies were undertaken with the Bt cotton hybrid viz. Ankur 3028 BG II in Kharif, 2016 and 2017 at Punjab Agriculture University, Regional Research Station, Bathinda to study the effect of Cotton leaf curl virus disease severity on yield parameters of Bt cotton in Punjab. The Bt cotton hybrid was raised under natural conditions in the field conditions in the first week of May. The symptoms of the CLCuD were critically examined after 100 days of sowing and 20 plants were tagged on the basis of the severity of the cotton leaf curl virus disease severity grade (0-VI) scale. The data of 5 randomly selected tagged plants of each grade i.e. Plant height (cm), Number of monopods and sympods, Number of bolls, Boll weight (g) and yield (kg/ha) were recorded.